KONSEP PENDIDIKAN ANAK SHALEH PERSPEKTIF ABDULLAH NASHIH ULWAN DAN RELEVANSINYA PADA PENDIDIKAN ANAK - Yanti Maya Sari, Arna (Yayasan Darussalam Bengkulu, 2021)
The purpose of this study was to obtain answers about the concept of pious children's education in Abdullah Nashih Ulwan's perspective and its relevance in Children's Education. This study uses the library research method, namely research that collects data and information with the help of various materials contained in the library where the source of data, namely the primary data source is the Book of Children's Education in Islam by Abdullah Nasih Ulwan which has been translated into Indonesian and several other complementary books. The data collection technique was carried out using the following steps: collecting literature related to the concept of children's education, classifying books based on primary book sources, confirming or crosschecking, then grouping data from Abdullah Nasih Ulwan's thoughts. The data analysis techniques are as follows: content analysis which utilizes data consisting of documented materials, descriptive analysis, namely the method used to describe or provide an overview of the object under study and then inductive analysis starts the data from empirical facts. The results of this study by Abdullah Nashih Ulwan's review are that children are obedient and serious in carrying out His commands and stay away from all His prohibitions (amar ma'ruf nahi mungkar) based on Islamic values, and make Islam is the religion, the Qur'an is the Imam, and the Messenger of Allah (saw) is. as a leader and role model. Meanwhile, the characteristics of a pious child in Abdullah Nashih Ulwan's view are Faith and fear of Allah SWT, and the Last Day, Loving the Messenger of Allah, and his Bait Expert, imitating the actions of his friends, doing good to both parents (birrul walidain), warning ma'ruf nahi munkar, establish prayer, fast, pay zakat, perform hajj if able, be patient in facing trials in life, not be arrogant, ignorant or indifferent, always speak politely and be polite to everyone.